Evaluation of tualang honey and propolis on vaginal flora in locally advanced cervical cancer patients undergoing chemoradiotherapy - Safruddin, Engku Ibrahim Syubli Engku (2018)
Cervical cancer is the most common cancer among women. The standard treatment consists of radiotherapy, chemotherapy and brachytherapy. Chemotherapy is invariably administered to all cervical cancer patients. Chemoradiotherapy agents often associated with side effects. Chemoradiotherapy induced immune system is one of the side effects despite of the hair loss, lost appetite which affects cervical cancer sufferers mostly. There is lack of knowledge in the field of microbiology that should focus on bacterial infection during the cytotoxic treatment with chemoradiotherapy. This prospective clinical trial was conducted to elucidate the effect of Tualang honey and propolis on the changes of the vaginal flora isolation in the high vaginal area during chemoradiotherapy treatment period. The in vivo study was embarked on to evaluate the reduction of bacterial growth during the standard chemoradiotherapy to cervical cancer patients. A total of 30 patients were successfully recruited (15 study arm, 15 control arm). In the study arm group, chemoradiotherapy was supplemented with additional apitherapy treatment, while the control arm group only received the chemoradiotherapy. High vaginal swab and high vaginal wash were collected before and after chemoradiotherapy from recruited patients to quantitate the bacterial growth, for five consecutive weeks of treatment. The changes in the bacterial growth were compared between the five weeks of treatment to determine the in vivo’s efficacy of Tualang honey and propolis. Various types of bacteria were isolated andidentified from samples, suggesting the alteration occurred in the vaginal ecosystem. Finding from this study also demonstrated that Tualang honey and propolis has potential as complementary treatment during chemoradiotherapy. Inhibition of bacterial growth were noted in patients treated with Tualang honey and propolis (study arm) compared to the untreated patients (control arm). The antibacterial effects of Tualang honey and propolis were subsequently proved via in vitro studies using bacteria that were isolated directly from cervical cancer patients. Two immunological markers namely CRP protein level and lymphocyte CD4+ cell count were tested whether correlated with the bioburden of bacteria. Finding showed that both CRP protein level (r=-0.3, p≤0.05) and lymphocyte CD4+ cell count (r=-0.37, p≤0.05) were not significant with the bioburden of bacteria. But for CRP protein, the results still showed a good result, and maybe can be tested further to confirm its role due to the low sample size in this research. For CD4+ cells, it cannot be used as a marker to monitor the bacterial infections because it was affected by chemoradiotherapy. In this study, Tualang honey and propolis can be used as a complementary treatment to prevent any bacterial infections during chemoradiotherapy treatment. Bacterial growth reduction can be seen in patients treated with Tualang honey and propolis, parallel with CRP protein level in patient’s body.